Consolidarea rezilienței sociale prin valorificarea capitalului uman: perspective regionale și naționale. desfășurarea cercetării în focus-grupuri - Mocanu, Ion (Editura USM, 2024)
The research presents the results obtained after conducting 9 focus groups in urban and rural locali-ties in the Republic of Moldova on the subject of social resilience and human capital. The study investigates the role of individual and community resources, educational attainment, health, civic engagement, and social networks in fostering resilience. The respondents gave their opinion on the major concerns and problems faced by the citizens of the Republic of Moldova, both at the local and regional level. Most respondents highlighted the importance of continuing education and training to improve the knowledge level of the community. Several responses emphasize the importance of returning young people to the community to contribute to its develop-ment. There is an urgent need for reforms in the health system to improve the health status of the population. From the answers received, the idea emerges that access to the top of the social hierarchy is closely related to political and social connections. There are localities where people are active and involved in solving commu-nity problems, and others where this involvement is less or even absent. We also aimed to research the common factors for the investigated localities that contribute to the population's resistance to social stress and crisis situations.
Strengthening social resilience by capitalizing on human capital: regional and national perspectives. conducting research in focus groups
Keywords: social resilience; human capital; socioeconomic challenges; security; regional crises; social stress; educational attainment; health; civic engagement; social networks